Stitch together: Creating ephemeral architecture through crochet - Al-Azzawe, Shams (My University, 2025)
Stitch Together explores the connections between ephemeral architecture and crocheting - how this craft can be used to create modular structures that are interactive for the user and revitalize in between spaces in the city. Ephemeral architecture challenges the permanence of architecture, redefining the urban space by its temporary and flexible nature (Borges Ferreira, 2024). The structures are adaptable to new contexts, meant to be assembled and disassembled (ArchDaily, 2023) and liven up the urban environment by having a function that is interactive for the user (Borges Ferreira, 2024). This is especially relevant for in between spaces in the urban context that often lack activity and interaction. In architecture, crocheting offers a seamless creation of 3D objects that are lightweight, flexible, and resilient. It also creates a tactile, soft and inviting materiality to touch (Baurmann, n.d.). Due to the crocheted fabric’s flexible nature, ability to create forms freely and many options for stitches, it is an interesting technique for applying ephemeral architecture. Its lightweightness makes it easy to move from place to place and its flexibility makes it easy to assemble and disassemble. The thesis translates the material properties and techniques within crocheting into architectural practice. It uncovers the range of the crocheting techniques, that are diverse and can create tensile structures effortlessly. Additionally, crochet chart patterns have been explored as a tool for modularity, illustrating the structure of the crochet pieces. The thesis begins with explorations about crochet stitches, techniques, and the chart language in relation to architecture and how it could be applied to different functions on the site, Esperantoplatsen. These functions, or as I call them architectural uses, are defined by a site analysis. These include climbing, enclosing, sitting and viewing. The uses were then analyzed in relation to the crocheting techniques to conclude different compatibilities. From this, the design proposal was developed, consisting of one design for each use that integrates different human senses. Esperantoplatsen was then transformed into an experience park, taken over by yarn.
Keywords: Ephemeral architecture, crochet, modularity and design for disassembly, soft architecture, in between spaces